ANALISIS SISTEM INFORMASI STMIK IKMI CIREBON MENGGUNAKAN WEBQUALITY (WEBQUAL) - Saefuddin, Asep; Suprapti, Tati; Wijaya, Yudhistira Arie (LPPM UNIKA Santo Thomas Medan, 2023)
This study focuses on the quality of STMIK IKMI Cirebon's website, which serves as an information system for the campus. The website provides information on various aspects of the school and can significantly impact user satisfaction. The study aims to measure the website's quality based on user perceptions using Webqual, a technique that measures usability, information, and interaction quality. The results can help improve the information system of the website and provide data on its quality. The study highlights the importance of website quality and user satisfaction, and the usefulness of Webqual as a tool for measuring website quality and improving user experience. By prioritizing website quality and user satisfaction, organizations can create more effective and efficient information systems that meet users' needs